Population and Development in the Sahel : Policy Choices to Catalyze a Demographic Dividend - Shekar, Meera (World Bank, Washington, DC, 2016)
The demographic transition in the Sahel region has been slower than that in the rest of the world. Although child mortality rates have declined in recent decades, they are still higher in West Africa than in other regions. Furthermore, the fertility decline has progressed very slowly, with some countries seeing stalls and others even an increase in birth rates. The speed with which this transition takes place has a critical impact on a population’s age structure and future potential for economic productivity. The current rates of change in the Sahelian sub region will make it unlikely that countries will achieve an age structure that will create a youth bulge of a healthy, well-nourished, and educated cohort ready to enter a modern labor market to capture a sizable demographic dividend. Once missed, this opportunity for a demographic dividend will not return. This analysis uses quantitative data triangulated with the qualitative findings and policy analyses to identify the triggers necessary to accelerate the demographic dividend in this sub region.